2013
DOI: 10.1097/iae.0b013e31828ac07d
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Methotrexate Can Induce Extended Remission in Some Patients in Noninfectious Uveitis

Abstract: In patients with uveitis and uveitic cystoid macular edema, intravitreal MTX can effectively improve visual acuity and reduce cystoid macular edema and, in some patients, allows the reduction of immunosuppressive therapy. Some patients relapse at 3 to 4 months, but a large proportion (73%) enter an extended period of remission of up to 18 months. This larger study extends the results obtained from previous smaller studies suggesting the viability of intravitreal methotrexate as a treatment option in uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 34 publications
4
41
1
2
Order By: Relevance
“…14,15 Previous studies have reported potent antiinflammatory properties of the intravitreal MTX in patients with noninfectious uveitis. 16,17 Moreover, intravitreal injection of MTX has less complication compared with the triamcinolone acetonide, another potent widely used anti-inflammatory agent. 9 Two studies reported the use of intra-silicone MTX for surgical indications other than intraocular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Previous studies have reported potent antiinflammatory properties of the intravitreal MTX in patients with noninfectious uveitis. 16,17 Moreover, intravitreal injection of MTX has less complication compared with the triamcinolone acetonide, another potent widely used anti-inflammatory agent. 9 Two studies reported the use of intra-silicone MTX for surgical indications other than intraocular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Has an excellent safety profile when injected into the eye Single 400 lg/0.1 mL dose : visual acuity in 79 % of treated eyes and ; the need for systemic therapy; in patients that relapsed after the first injection, a second injection was followed by remission of up to 18 months [25] Sirolimus Subconjunctival (1320 lg) and intravitreal (352 lg) injections at days 0, 60 and 120 appeared to be safe and well tolerated, and : visual acuity, ; inflammation and ; the need for systemic corticosteroids [26] Bimonthly 440 lg injections ; vitreous haze (primary endpoint) in 60 % of patients [27] IOP intraocular pressure, : increase(d)/improved, ; decrease(d) the treatment of choice for ameliorating signs and symptoms of sight-threatening ocular inflammation (Fig. 1); however, their use is limited by their well-known adverse event profiles.…”
Section: Intermediate and Posterior Uveitis Often Requires An Aggressmentioning
confidence: 98%
“…A more recent paper described a multicenter, retrospective interventional case series of patients with non-infectious uveitis treated with intravitreal MTX [55]. Thirty-eight eyes of 30 patients were enrolled, for a total of 54 intravitreal injections of MTX at a dose of 400 mg in 0.1 ml.…”
Section: Intravitreal Mtxmentioning
confidence: 99%